Sex identification in canarium odontophyllum miq. (Dabai) using random amplified polymorphic DNA (RAPD) marker - Ting, Jen Ching (Universiti Malaysia Sarawak, UNIMAS, 2008)
Canarium odontophyllum Miq. is a perennial plant native to Malaysia, Indonesia and Philippines. The pistillate plants bear fruits twice a year and are more preferable than staminate plants. Thus, sex determination in Canarium odontophyllum at seedling stage is very important for crop improvement processes because it accelerates the identification of fruitful pistillate plants. In this study, Random Amplified Polymorphic DNA (RAPD) technique was used to amplify DNA segments, with the objective of finding molecular markers associated to sex determination locus in this species. DNA was isolated from one male and three female Dabai trees and subjected to RAPD analysis. Of 52 RAPD primers, one primer (OPL – 03) produced an approximately 1,000 bp amplification band detectable in all pistillate plants, while absent in the staminate plants. The exclusiveness of this female-specific diagnostic band could be used in a breeding program to screen the gender of Dabai trees long before they reach reproductive maturity, resulting in considerable savings of time and economic resources.